The project runway: Cheryl Chong on getting your social initiative off the ground - Chong, Cheryl (Institutional Knowledge at Singapore Management University, 2017)
Cheryl Chong is co-founder of The Social Co., the team behind the 50 For 50 project that brought together more than 80 young people under the age of 35, and 70 corporations to raise awareness of and funds for lesserknown causes such as mental health, suicide prevention and charities that serve those with physical and mental disabilities. Cheryl currently chairs the Young Women's Leadership Connection (YWLC) and lends a hand in programme development at Jia Foundation, a family foundation established by the Lim and Lin families. In her day job, she heads the private investor division of equity and debt crowdfunding platform, FundedHere. Here are Cheryl’s tips on how to give your social initiative a roaring headstart.